Students' Comunication Perspective in Online Listening Subjects - Puspitasari, Eri; Sangkala, Ismail; Ariana (FKIP Unismuh Makassar, 2022)
This study aimed to discover students' communication perspectives in online listening subjects. The method used in this research was qualitative method in the kind of phenomenological research. The research instrument to collect the data was a semi-structured interview. The subjects of this study were third-semester students of the English Education Department, Faculty of Teacher Training and Education, Universitas Muhammadiyah Makassar.Based on the results of this study, the perspective of student communication in online listening classes, students stated that the way the lecturer conveys material in the online listening class is direct via Zoom or Google meet. Meanwhile, in terms of interaction, some students answered that communication was done in writing on WhatsApp. Then, In terms of delivering feedback, almost all students mentioned that the lecturer delivered it in groups (one class). Whereas in terms of doing assignments students prefer to do them individually. Most students have a good opinion after studying these topics, and it helps them understand many situations in real life. Furthermore, most of the students mentioned that these themes influenced their understanding of culture because they heard how languages are in other countries. especially on differences in accent and pronunciation.